ENT 600 : Safety Vest / Muhammad Hazim Ismail ... [et al.] - Ismail, Muhammad Hazim; Ramlan, Danial Syaraani; Yassin, Ahmad Niza (2018)
The goal of this project is to develop and study a device that can detect pressure and send the data over a wireless transmission. Wireless hands-free technology is rapidly adapting to a variety of technology today. The purpose of this project was to take the "Officer Down" protocol and simplify it into a device that handles the procedure without user input. The solution was a body vest that is worn under the current equipment and detects harmful attacks. It then reports these attacks back to the station. Currently, the police use a button attached to the belt to alert the dispatcher if there is a problem. However there may be situations in which the officer becomes incapacitated or unable to alert the proper channels. It is possible to design sensors and equipment that will make the users that much safer.